Patterned LIG strain sensor for optimizing stress distribution and preparation method thereof

By designing dot-line patterned structures and combining laser-induced composite material properties of graphene and PDMS, the shortcomings in the patterned LIG strain sensors in the prior art are solved, and the strain sensing effect with high sensitivity and long-term stability are achieved.

CN119845132APending Publication Date: 2025-04-18ZHENGZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510059652.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When existing patterned LIG strain sensors realize complex pattern design, there are problems of resolution, processing efficiency and cost-effectiveness, making it difficult to optimize stress distribution and improve sensing performance.

Method used

By designing dot-line patterned structures, combining the composite properties of laser-induced graphene and PDMS, a patterned LIG strain sensor with high linearity and high sensitivity was prepared using laser induction technology and transfer technology.

Benefits of technology

The stress distribution optimization is achieved, which significantly enhances the sensor's ability to recognize complex strain patterns, improves sensing performance and service life, and simplifies the preparation process and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119845132A_ABST
    Figure CN119845132A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flexible strain sensors, in particular to a patterned laser-induced graphene (LIG) strain sensor for optimizing stress distribution and a preparation method thereof. Comprising a polydimethylsiloxane (PDMS) substrate, an embedded dot-line patterned structure is arranged on the upper surface of the PDMS substrate, the patterned structure is a laser-induced graphene material, and the laser-induced graphene material is generated through a laser-induced process. The two ends of the patterned structure are provided with electrodes, and the electrodes are coated with conductive silver paste. The preparation method comprises the following steps: ablating a polyimide film pasted on a glass slide through a laser induction technology, inducing to generate three-dimensional porous graphene, pouring PDMS, carrying out vacuum degassing and curing processes, and finally stripping and removing the glass slide and polyimide to obtain the LIG-PDMS flexible strain sensor. According to the invention, a patterned LIG strain sensor can be rapidly prepared, the sensitivity (GF) reaches up to 207.47, and the strain monitoring range can reach 28%. The method can be applied to the fields of wearable electronic equipment and medical monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of flexible strain sensors, and in particular to a patterned LIG strain sensor with optimized stress distribution and a preparation method thereof. Background Art

[0002] With the rapid advancement of flexible electronics and wearable technology, the demand for highly sensitive and stable strain sensors is growing, especially in the fields of health monitoring, human-computer interaction and smart clothing. Traditional strain sensors often cannot meet high standards in terms of flexibility, durability and sensing accuracy, which limits their application potential in dynamic and complex environments.

[0003] In recent years, graphene has become an ideal material for the development of flexible strain sensors due to its excellent conductivity, high strength and outstanding flexibility. In particular, the rise of laser-induced graphene (LIG) technology, which directly converts polymer precursors into porous graphene structures through selective laser treatment, not only simplifies the preparation process, but also allows precise control of the microstructure of the sensor, thereby optimizing its performance. Polydimethylsiloxane (PDMS), as a commonly used flexible matrix material, is often compounded with graphene to form a sensor device with good mechanical compliance due to its biocompatibility, low Young's modulus and easy processing.

[0004] Although LIG-PDMS composites have shown great potential in the field of flexible strain sensors, there are still technical difficulties in realizing complex patterning designs. Existing patterning technologies are often limited by resolution, processing efficiency and cost-effectiveness, making it difficult to efficiently and accurately construct complex patterns that can both optimize stress distribution and improve sensing performance. In addition, how to maintain the stability and reliability of the sensor in long-term use while ensuring its high sensitivity and rapid response is also a key issue that needs to be solved urgently.

[0005] Therefore, the development of a patterned LIG strain sensor that can optimize stress distribution and its efficient preparation method aims to break through the limitations of existing technologies. Through sophisticated laser processing strategies and material design, precise regulation of the sensor structure can not only significantly enhance its ability to recognize complex strain patterns, but also improve the overall sensing performance and service life, providing strong support for the in-depth development of flexible electronic technology. This invention focuses on optimizing pattern design and laser parameters in order to achieve unprecedented strain sensing accuracy and application flexibility to meet the diversified needs of future intelligent and personalized devices. Summary of the invention

[0006] In order to overcome the defects in the above-mentioned prior art, the present invention provides a patterned LIG strain sensor with optimized stress distribution and a preparation method thereof, wherein graphene generated by a laser induced process on polyimide is transferred by PDMS to produce a flexible strain sensor with high linearity and high sensitivity.

[0007] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0008] A patterned LIG strain sensor for optimizing stress distribution, characterized in that it includes a laser-induced graphene layer, a PDMS flexible substrate and a conductive silver paste lead electrode, wherein the laser-induced graphene layer is located on the upper surface of the PDMS flexible substrate, and the graphene layer is embedded in the PDMS flexible substrate.

[0009] Preferably, the laser induced graphene layer is a dot-line patterned structure, the length of the dot-line patterned structure is 46mm±2mm, and the width is 10mm±2mm; the dot-line patterned structure is composed of a single or multiple broken lines with a line width of 0.8mm±0.2mm, and solid circles with a diameter of 1.2mm±0.2mm are arranged at the inflection points of the broken lines.

[0010] Preferably, the dot-line patterned structure is an array structure composed of a combination of folded lines, straight lines, sinusoidal lines, square wave lines and dots.

[0011] Preferably, lead electrodes are provided at both ends of the dot-line patterned structure, and the lead electrodes are made by brushing with conductive silver paste.

[0012] The resistance value of the sensor is directly proportional to the tensile strain.

[0013] The laser-induced graphene layer is generated by a laser induction process.

[0014] Preferably, the laser used in the laser induction process is a semiconductor laser with a blue light wavelength of 455nm±5nm, and the engraving parameters of the semiconductor laser are adjustable.

[0015] A method for preparing a patterned LIG strain sensor with optimized stress distribution comprises the following steps:

[0016] Step S1: cutting a polyimide film of the same size as the glass slide, applying UV curing glue on a clean glass slide, pasting the polyimide film on the glass slide, and then curing it under UV light to obtain a polyimide-glass slide structure;

[0017] Step S2: using a laser induction process, preparing a patterned laser-induced graphene layer on the surface of the polyimide-glass slide structure obtained in step S1 to obtain a LIG-polyimide-glass slide structure;

[0018] Step S3: The two components of the PDMS solution are mixed and stirred evenly in a ratio of prepolymer: curing agent = 10:1, and after removing bubbles in a vacuum drying oven, they are poured on the upper surface of the LIG-polyimide-glass slide structure obtained in step S2, and then placed in a vacuum drying oven, and the vacuum condition is maintained for 20 to 40 minutes, and then heated and cured at 70 to 80° C. for 90 to 120 minutes to obtain a PDMS-LIG-polyimide-glass slide structure;

[0019] Step S4: peeling off and removing the glass slide and polyimide in the combined structure obtained in step S3 in sequence to obtain a patterned LIG-PDMS structure;

[0020] Step S5: Conductive silver paint is applied to both ends of the LIG pattern obtained in step S4 to form lead electrodes, thereby obtaining a patterned LIG strain sensor.

[0021] The beneficial effects of the present invention are:

[0022] 1. Stress distribution optimization: By designing a dot-line patterned structure, the present invention can more effectively disperse and guide stress, ensuring that the sensor responds more uniformly and sensitively under various strain conditions. This optimized design helps improve the accuracy and reliability of the sensor, especially in application scenarios that monitor complex or non-uniform strain distribution.

[0023] 2. Enhanced sensing performance: By utilizing the composite material properties of LIG and PDMS and combining them with patterning technology, the sensor can maintain high flexibility while improving the strain sensing sensitivity and strain detection range. The sensitivity (GF) is as high as 207.47, and the strain monitoring range can reach 28%.

[0024] 3. Improve stability and durability: Through precise control of laser parameters and optimization of material interfaces, the strain sensor of the present invention can still maintain good stability after being used for up to 8,000 cycles of loading.

[0025] 4. Simplify the preparation process: The preparation method is efficient, low-cost, and does not require a special gas environment. It can complete the preparation and patterning of graphene components in a single step, which significantly shortens the preparation cycle and reduces production costs compared to traditional methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of the structure of a patterned LIG strain sensor for optimizing stress distribution according to the present invention;

[0027] Figure 2 Schematic diagram of the dot-line patterned structure and lead electrodes of the LIG strain sensor;

[0028] Figure 3A schematic diagram of the preparation process of a patterned LIG strain sensor with optimized stress distribution according to the present invention;

[0029] Figure 4 The time-△R / R0 curves of the patterned LIG strain sensor with different tensile strains according to Example 2 of the present invention;

[0030] Figure 5 3. The strain-△R / R0 curves of the patterned LIG strain sensor of Example 2 of the present invention at different tensile strains;

[0031] Figure 6 3 is a time-△R / R0 curve of the response and recovery of the patterned LIG strain sensor of Example 2 of the present invention;

[0032] Figure 7 The time-△R / R0 curves of the patterned LIG strain sensor at different cyclic loading frequencies according to Example 2 of the present invention;

[0033] Figure 8 The time-△R / R0 curve of the patterned LIG strain sensor of Example 2 of the present invention after 8000 cycles of loading;

[0034] Fig. 9 This is a measured graph of the pulse signal of the patterned LIG strain sensor according to Example 3 of the present invention.

[0035] In the figure: laser induced graphene layer 1; PDMS flexible substrate 2; conductive silver paste 3; patterned structure 4 lead electrode 5. DETAILED DESCRIPTION

[0036] In order to better illustrate the content of the present invention, the following is a detailed description with reference to the drawings and embodiments. It should be pointed out that the description in the embodiments is only used to explain the scheme of the present invention and is not used to limit the present invention.

[0037] Example 1

[0038] The present invention provides a patterned LIG strain sensor with optimized stress distribution, and its structural schematic diagram is shown in FIG. Figure 1 As shown, it includes a laser induced graphene layer 1, a PDMS flexible substrate 2, and a conductive silver paste 3, wherein the laser induced graphene layer 1 is located on the upper surface of the PDMS flexible substrate 2;

[0039] The dot-line patterned structure and lead electrode schematic of the LIG strain sensor are shown in Figure 2 As shown, lead electrodes 5 are provided at both ends of the patterned structure 4, and the surface of the lead electrodes is coated with conductive silver paste;

[0040] The laser induced graphene layer of the patterned LIG strain sensor described in the present invention is made by the laser induction process.

[0041] The laser induced graphene layer of the present invention is embedded in the PDMS flexible substrate, and the embedding depth of the laser induced graphene layer is preferably 50 to 200 μm, more preferably 70 to 110 μm, and most preferably 100 μm; the thickness of the PDMS flexible substrate is preferably 500 to 2000 μm, more preferably 900 to 1200 μm, and most preferably 1000 μm.

[0042] The dot-line patterned structure described in the present invention is composed of folded lines, straight lines, sinusoidal lines, square-wave lines and dots, but is not limited to the array structure composed of the above line and dot combinations.

[0043] In the patterned LIG strain sensor for optimizing stress distribution described in the present invention, the laser induced graphene layer is a dot-line patterned structure. Preferably, the dot-line patterned structure has a length of 46 mm ± 2 mm and a width of 10 mm ± 2 mm. Preferably, the dot-line patterned structure is composed of a single or multiple broken lines with a line width of 0.8 mm ± 0.2 mm. Preferably, a solid circle with a diameter of 1.2 mm ± 0.2 mm is provided at the inflection point of the broken line.

[0044] The laser used in the laser induction process of the present invention is a semiconductor laser with a blue light wavelength of 455nm±5nm. Preferably, the parameters of the semiconductor laser are set as follows: power 9-23% (5.5W), engraving speed 200-500mm / min, engraving line number 9-19mm -1 , spot engraving time 6 ~ 18ms, focus position 50mm ± 5mm; optimal, the parameters of the semiconductor laser are set as: power 21% (5.5W), engraving speed 400mm / min, engraving line number 17mm -1 , spot engraving time 12ms, focus position 50mm.

[0045] The present invention provides a method for preparing a patterned LIG strain sensor with optimized stress distribution. The schematic diagram of the preparation process is shown in FIG. Figure 3 As shown, the following steps are included:

[0046] Step S1: cutting a polyimide film of the same size as the glass slide, applying UV curing glue on a clean glass slide, pasting the polyimide film on the glass slide, and then curing it under UV light to obtain a polyimide-glass slide structure;

[0047] Step S2: using a laser induction process, preparing a patterned laser-induced graphene layer on the surface of the polyimide-glass slide structure obtained in step S1 to obtain a LIG-polyimide-glass slide structure;

[0048] Step S3: The two components of the PDMS solution are mixed and stirred evenly in a ratio of prepolymer: curing agent = 10:1, and after removing bubbles in a vacuum drying oven, they are poured on the upper surface of the LIG-polyimide-glass slide structure obtained in step S2, and then placed in a vacuum drying oven, maintained under vacuum conditions for 20 to 40 minutes, and then heated and cured at 70 to 80° C. for 90 to 120 minutes to obtain a PDMS-LIG-polyimide-glass slide structure;

[0049] Step S4: peeling off and removing the glass slide and polyimide in the combined structure obtained in step S3 in sequence to obtain a patterned LIG-PDMS structure;

[0050] Step S5: Conductive silver paint is applied to both ends of the laser-induced graphene pattern obtained in step S4 to make lead electrodes, thereby obtaining a patterned LIG strain sensor.

[0051] Example 2

[0052] Cut a polyimide film of the same size as the glass slide, apply UV curing glue on a clean glass slide, and stick the polyimide film to the glass slide, and then cure it under UV light to obtain a polyimide-glass slide structure;

[0053] The engraving pattern is drawn using computer drawing software; the dot-line patterned structure is 46 mm long and 10 mm wide; it is composed of 4 broken lines with a length of 0.8 mm and a width of 0.8 mm, and a solid circle with a diameter of 1.2 mm is provided at the inflection point of the broken line; the size of the connecting electrode is 10 mm×10 mm.

[0054] Adjust the laser focus position so that the laser emission point is 50mm away from the surface of the polyimide film; set the laser engraving parameters: power 21% (5.5W), engraving speed 400mm / min, engraving line number 17mm -1 , the spot engraving time is 12ms; the dot-line patterning size is set as follows: length 46mm, width 10mm; a dot-line patterned laser-induced graphene layer is prepared on the surface of the polyimide-glass slide structure by laser induction process to obtain a LIG-polyimide-glass slide structure;

[0055] Wrap a circle of tape around the obtained LIG-polyimide-glass slide structure; mix and stir the two components of the PDMS solution in a ratio of prepolymer: curing agent = 10:1, remove bubbles in a vacuum drying oven, take 2.5g of the PDMS mixed solution and pour it into the LIG-polyimide-glass slide structure surrounded by the tape; put it into a vacuum drying oven, maintain the vacuum condition for 40 minutes, and heat and cure it at 80°C for 120 minutes to obtain a PDMS-LIG-polyimide-glass slide structure;

[0056] The tape surrounding the PDMS is removed, and the glass slide and polyimide in the combined structure are peeled off and removed in sequence to obtain a patterned LIG-PDMS structure;

[0057] A layer of conductive silver paint is applied on both ends of the LIG dot-line pattern, and after solidification, lead electrodes are made to obtain a patterned LIG strain sensor.

[0058] Conductive copper tapes were attached to the lead electrodes at both ends of the prepared patterned LIG strain sensor as wires, and the tensile strain performance was tested on a flexible device test platform. The sensor was pre-stretched for 100 loading-unloading cycles at a maximum strain of 30%.

[0059] Testing the sensing performance of patterned LIG strain sensors:

[0060] Figure 4 The time-△R / R0 curve of the patterned LIG strain sensor at different tensile strains. It can be seen from the figure that the sensor corresponds to different △R / R0 values ​​at different strain sizes and has consistency and recoverability at the same strain.

[0061] Figure 5 The strain-△R / R0 curves of the patterned LIG strain sensor at different tensile strains show that the resistance value of the sensor is in direct proportion to the tensile strain, and the linear correlation is strong, which is 0.9918 and 0.9905, very close to 1. The maximum strain range is 28%, and the sensitivity (GF) is 116.42 in the strain range of 0-15%, and the sensitivity (GF) is as high as 207.47 in the range of 15-28%.

[0062] Figure 6 The time-△R / R0 curve of the response and recovery of the patterned LIG strain sensor. It can be seen from the figure that the sensor can respond and recover quickly to strain, with a response time of 249ms and a recovery time of 295ms.

[0063] Figure 7 : The time-△R / R0 curve of the patterned LIG strain sensor at different cyclic loading frequencies. It can be seen from the figure that the sensor has the detection capability for cyclic loading frequencies of 0.1 to 1 Hz.

[0064] Figure 8 The time-△R / R0 curve of the patterned LIG strain sensor after 8000 cycles of loading is shown in the figure. As can be seen from the figure, under the 8000 cycles of loading test, the change of △R / R0 from the beginning to the end is small, indicating that the sensor has stable performance and has stability and reliability for long-term use.

[0065] Example 3

[0066] according to Figure 3 Preparation process shown; set laser engraving parameters: power 21% (5.5W), engraving speed 400mm / min, engraving line number 17mm -1 , spot engraving time 12ms; set the dot and line patterning size: length 46mm, width 10mm; prepare patterned LIG strain sensor.

[0067] The patterned LIG strain sensor was pasted on the wrist where the pulse beats, and the real-time resistance signal of the patterned LIG strain sensor was tested using a Keithley 2400 high-precision digital source meter. Fig. 9 The figure shows the measured pulse signal of the subject. As can be seen from the figure, the main peak and maximum point, secondary trough and secondary peak of each pulse wave are clearly identifiable.

[0068] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A patterned LIG strain sensor with optimized stress distribution, characterized in that: The invention comprises a laser-induced graphene layer, a PDMS flexible substrate and a lead electrode. The laser-induced graphene layer is located on the upper surface of the PDMS flexible substrate, and the graphene layer is embedded in the PDMS flexible substrate.

2. The patterned LIG strain sensor according to claim 1, wherein The laser-induced graphene layer is a dot-line patterned structure, which has a length of 46 mm ± 2 mm and a width of 10 mm ± 2 mm; the dot-line patterned structure is composed of a single or multiple broken lines with a line width of 0.8 mm ± 0.2 mm, and solid circles with a diameter of 1.2 mm ± 0.2 mm are arranged at the inflection points of the broken lines.

3. The patterned LIG strain sensor according to claim 1, wherein The dot-line patterned structure is an array structure composed of a combination of a folded line, a straight line, a sinusoidal line, a square wave line and dots.

4. The patterned LIG strain sensor according to claim 1, wherein: Lead electrodes are arranged at both ends of the dot-line patterned structure, and conductive silver paste is brushed on the surface of the lead electrodes.

5. The patterned LIG strain sensor according to claim 1, wherein: The resistance value of the sensor is directly proportional to the tensile strain.

6. The patterned LIG strain sensor according to claim 1, wherein: The laser-induced graphene layer is made by a laser induction process.

7. The laser induction process according to claim 6, characterized in that: The laser used in the laser induction process is a semiconductor laser with a blue light wavelength of 455nm±5nm. The engraving parameters of the semiconductor laser are adjustable.

8. A method for preparing a patterned LIG strain sensor with optimized stress distribution, characterized in that: The steps include: Step S1: cutting a polyimide film of the same size as the glass slide, applying UV curing glue on a clean glass slide, pasting the polyimide film on the glass slide, and then curing it under UV light to obtain a polyimide-glass slide structure; Step S2: using a laser induction process, preparing a patterned laser-induced graphene layer on the surface of the polyimide-glass slide structure obtained in step S1 to obtain a LIG-polyimide-glass slide structure; Step S3: The two components of the PDMS solution are mixed and stirred evenly in a ratio of prepolymer: curing agent = 10:1, and after removing bubbles in a vacuum drying oven, they are poured on the upper surface of the LIG-polyimide-glass slide structure obtained in step S2, and then placed in a vacuum drying oven, and the vacuum condition is maintained for 20 to 40 minutes, and then heated and cured at 70 to 80° C. for 90 to 120 minutes to obtain a PDMS-LIG-polyimide-glass slide structure; Step S4: peeling off and removing the glass slide and polyimide in the combined structure obtained in step S3 in sequence to obtain a patterned LIG-PDMS structure; Step S5: Conductive silver paint is applied to both ends of the laser-induced graphene pattern obtained in step S4 to make lead electrodes, thereby obtaining a patterned LIG strain sensor.

Citation Information

Cited By

  • Flexible deep sea pressure sensor and corresponding fully-integrated temperature-depth sensing system

    CN121498946A

  • A fabric-based bifunctional graphene sensor and a preparation method and application thereof

    CN122881769A